Cis-9, Trans-11 CLA Alleviates Lipopolysaccharide-Induced Depression of Fatty Acid Synthesis by Inhibiting Oxidative Stress and Autophagy in Bovine Mammary Epithelial Cells - Nana Ma; Guozhen Wei; Hongzhu Zhang; Hongyu Dai; Animesh Chandra Roy; Xiaoli Shi; Guangjun Chang; Xiangzhen Shen (MDPI AG, 2021)
Lipopolysaccharide (LPS) is the dominating endotoxin of Gram-negative bacteria, which can cause mastitis. Bovine mammary epithelial cells (BMECs), as major components of the mammary gland, usually suffer LPS challenge. Cis-9, trans-11 conjugated linoleic acid (CLA) has been reported to have anti-inflammatory characteristics, while its anti-oxidative ability to maintain cellular homeostasis in BMECs under LPS challenge is limited. Therefore, we studied whether cis-9, trans-11 CLA can restore the disturbance of cellular homeostasis indicated by the redox status and autophagy level caused by LPS and have an effect on cellular function- milk fat metabolism. For oxidative stress, LPS challenge promoted the formation of reactive oxygen species (ROS) and thiobarbituric acid reactive substances (TBARS) and decreased the concentration of glutathione. Anti-oxidative signaling regulated by transcription factor nuclear factor, erythroid 2 like 2 (Nrf2) was also depressed by LPS at the mRNA and protein level. However, cis-9, trans-11 CLA pretreatment downregulated the formation of ROS and TBARS and upregulated the expression of antioxidative enzymes. As a part of innate immunity, autophagy was also motivated by LPS challenge, while CLA decreased the autophagy level. LPS and H2O2 inhibited milk fat synthesis-related transcription factor sterol regulatory element binding protein (SREBP1), peroxisome proliferator activated receptor gamma (PPARG) and their downstream enzymes. Furthermore, 50 uM cis-9, trans-11 CLA promoted the mRNA and protein abundance of milk fat synthesis-related genes and lipid droplet formation in BMECs. In conclusion, LPS challenge disturbed the cellular homeostasis and depressed milk fat synthesis in BMECs; while cis-9, trans-11 CLA alleviated oxidative stress and decreased autophagy level, thus promoting milk fat synthesis, which offers a natural therapeutic strategy for mastitis.